1977
DOI: 10.1128/iai.16.2.518-521.1977
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of cellular and humoral immunity in guinea pigs after infection with Coxiella burnetii administered in small-particle aerosols

Abstract: The development of humoral and cell-mediated immune responses was studied in guinea pigs infected with Coxiella burnetii administered in small-particle aerosols. Direct macrophage migration inhibition was observed in cultured peritoneal exudate cells as early as 3 days after exposure. Maximum inhibition of macrophages cultured with phase I or II antigen occurred 14 to 21 days postexposure and persisted through 35 days. This inhibitory action was no longer detectable at 42 days. Serum antibody to the phase II a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…High titers of phase II antibodies were detected in the sera of mice immunized with 30 or 300 pLg of CMR. In agreement with previous studies (11,16,17), the production of phase II antibodies was rapid (day 4) and persisted until day 21. The level of phase II antibody from these animals was similar to that detected in the sera of mice inoculated with whole cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…High titers of phase II antibodies were detected in the sera of mice immunized with 30 or 300 pLg of CMR. In agreement with previous studies (11,16,17), the production of phase II antibodies was rapid (day 4) and persisted until day 21. The level of phase II antibody from these animals was similar to that detected in the sera of mice inoculated with whole cells.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown that vaccines prepared from suspensions of killed whole cells of C. burnetii induce humoral immunity against phase I and phase II antigens in both humans (17,20,21) and experimental animals (26,27). In addition, cell-mediated immunity, as measured by delayed hypersensitivity, has been observed in vaccinated guinea pigs (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guinea pig has been used extensively as an experimental model for C. burnetii infections (9,17,21,22,30) and is still the model system of choice for the initial evaluation of Q-fever vaccines. The pathogenesis of the Nine Mile strain has been examined in some detail (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that phase II cells are much less effective vaccines than are phase I cells (22). Roles for both antibody (16) and cellmediated immunity (15,18) as protective mechanisms in Q fever have been proposed. Although the accessibility of surface components to T-cell recognition sites was not examined here, it seems likely that if antibody cannot reach the surfaces of the microbes, neither would immune cells be able to contact C. burnetii surface proteins.…”
Section: Discussionmentioning
confidence: 99%